(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Alopecia means loss of hair. Androgenetic alopecia (AGA) now called as patterned hair loss (male pattern hair loss; MPHL, female pattern hair loss; FPHL) is caused by androgens in a predisposed individual. It is modulated by factors like age, sex, genes, smoking, and alcohol. If untreated this leads to psychological problems like stress, anxiety, depression and decrease self-confidence which affect quality of life. A thorough clinical examination and a certain hormonal estimation could reveal levels of androgens, hyperandrogenism, adrenal hyperplasia, (PCOS) polycystic ovarian syndrome, and ovarian/adrenal tumors. A simple Trichoscopy could show the typical picture of hair miniaturization commonly seen in this condition. Finally, a biopsy of the scalp could help in clinching conclusive diagnosis. Out of the many treatments at our disposal, the non-pharmacologic methods like temporary camouflage techniques, synthetic hair wigs, hair-thickening fibers, hair weaving, pigmented powders are useful. Semi-permanent options like scalp micro-pigmentation (thorough tattooing) are useful to enhance appearances. Presently the United States Food and Drug Administration (USFDA) approved pharmacologic treatments are Minoxidil and Finasteride. The non-USFDA approved methods of treatments like various surgical procedures [hair transplantation]: follicular unit transplantation (FUT), follicular unit extraction (FUE), microneedling, light therapy, indigenous medicines, Platelet-Rich Plasma (PRP), and various loco-regional hair care practices are in vogue. The outcome of this review is to offer the latest update and insights into the newer novel therapies in patterned hair loss. Also, the patients could enhance their knowledge about the condition, the benefits and prognosis of each treatment.